Occupational particulate matter (PM2.5) exposure and its relation with lung function performance among workers in automotive component manufacturing industry / Noraini Mohd Judi - Mohd Judi, Noraini (2012)
Background: Workers are operating machine in the automotive component manufacturing industry could produces respirable particulate from the process of buffing, welding, damper assembly and band saw. Objective: To determine the occupational PM2.5 concentration exposure and its relation with lung function performance among workers in automotive component manufacturing industry. Methodology: A cross- sectional study was carried out among sixty workers. The personal exposure of PM2 s was measured for both groups by using personal air sampling pump during working hours within 8-9 hours. The lung function performances were assessed to measure the Forced Vital Capacity (FVC), Forced Expiratory Volume in 1 second (FEV1) and FEV1 I FVC ratio. The respiratory symptom was determined by using modified questionnaire based on American Thoracic Society. Results: The mean of PM 2.5 concentration exposure to exposed group is (1.403 mg/ rrr') which were higher compared to unexposed group of workers (0.668 mg/ rn"). PM25 exposure between exposed and unexposed group of workers shows a significant difference at (p< 0.001 ). Exposed group of workers had significantly lower percentage of predicted values of FVC, FEV1 and FEV1/ FVC than unexposed group of workers. However, only variable FEV1/ FVC was significantly difference between these two groups (p=0.02). There is no correlation between (PM25) concentration exposure and lung function performance among workers in automotive components manufacturing industry. Only breathlessness has significant difference between exposed and unexposed group of workers at (p=0.01 ). Conclusion: Findings showed that occupational PM25 exposure was not related with the lung function performance among workers in automotive component manufacturing industry.